Bounds on Codes Correcting Periodic Errors Blockwise - Pankaj Kr Das (Institute of Advanced Engineering and Science, 2013)
This paper presents a necessary and suﬃcient condition on the number of paritycheck digits required for the existence of codes correcting periodic errors of diﬀerent ordersin diﬀerent blocks of a code. An example of such a code has also been provided.DOI: http://dx.doi.org/10.11591/ij-ict.v2i1.1332